1982
DOI: 10.1007/bf01258003
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic proliferation in the auditory cortex of the young adult rat following callosal lesions

Abstract: The long-term effects of partial deafferentation in the neocortex of adult rats were studied in four-month old rats in which the corpus callosum had been completely sectioned when they were one-month old. Quantitative light microscopy was used to identify morphological changes in the auditory cortex resulting from the loss of established callosal connections. Particular attention was directed at those cortical layers known to receive the heaviest callosal projection (layers II and III) and at neurons known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…For example, the ratio of asymmetrical, axospinous to axodendritic synapses in the neuropil of layer I11 in rat auditory cortex is 84: 16, whereas the ratio for synapses made by extrinsic callosal afferents to this region is significantly different at 93:7 (x2 test P < 0.01) (Vaughan and Peters, 1985). These findings, indicate that axonal pathways are highly selective for their postsynaptic elements, a proposition consistent with additional results from the same region of cortex: At survival times of 3 months after a callosal lesion, thalamic afferents that have grown into the deafferented region (Vaughan and Foundas, 1982) form synapses at essentially the same spine to shaft ratio of 80:20 as reported for thalamic afferents in normal animals (Vaughan and Peters, 1985). Previous results from layers 111, IV, and V of mouse primary somatosensory cortex, where the ratio of asymmetrical, axospinous to axodendritic synapses in the neuropil approximates 60:40, exhibit ratios of 87:13 for intrinsic synapses made by corticocortical projection neurons (Elhanany and White, 1990), and 8:92 for those made by corticothalamic projection neurons (White and Keller, 1987).…”
Section: Specificity Of D O S a L Synaptic Relationshipssupporting
confidence: 80%
“…For example, the ratio of asymmetrical, axospinous to axodendritic synapses in the neuropil of layer I11 in rat auditory cortex is 84: 16, whereas the ratio for synapses made by extrinsic callosal afferents to this region is significantly different at 93:7 (x2 test P < 0.01) (Vaughan and Peters, 1985). These findings, indicate that axonal pathways are highly selective for their postsynaptic elements, a proposition consistent with additional results from the same region of cortex: At survival times of 3 months after a callosal lesion, thalamic afferents that have grown into the deafferented region (Vaughan and Foundas, 1982) form synapses at essentially the same spine to shaft ratio of 80:20 as reported for thalamic afferents in normal animals (Vaughan and Peters, 1985). Previous results from layers 111, IV, and V of mouse primary somatosensory cortex, where the ratio of asymmetrical, axospinous to axodendritic synapses in the neuropil approximates 60:40, exhibit ratios of 87:13 for intrinsic synapses made by corticocortical projection neurons (Elhanany and White, 1990), and 8:92 for those made by corticothalamic projection neurons (White and Keller, 1987).…”
Section: Specificity Of D O S a L Synaptic Relationshipssupporting
confidence: 80%
“…The patches are widest in layer II/III where the densest degeneration occurs, they become narrower in layer IV where there is little degeneration, and expand inqayers V and VI as the amount of degeneration increases again. That the amount of degeneration is greatest in the supragranular layers of rat auditory cortex has been confirmed by Vaughan & Foundas (1982), who carried out a quantitative electron microscopic study of the distribution of synapsing and degenerating callosal axon terminals. They found that the highest density of these terminals was within lower layer I and layer II/III, with very few degenerating terminals in layer IV.…”
Section: Discussionmentioning
confidence: 72%
“…Jacobson, 1966;Lund& Lund, 1970;Wise & Jones, 1976;Cusick & Lund, 1981;Vaughan & Foundas, 1982;Vaughan, 1982). In an earlier study (Cipolloni & Peters, 1979) we used the Fink-Heimer (1967) silver staining technique to examine the distribution of degenerating terminals and preterminals of callosal fibres in the posterior neocortex of the rat.…”
Section: Introductionmentioning
confidence: 99%
“…Since the focus of this study is on thalamocortical transmission, field potentials recordings were made in the middle depths of cortex (mean depth from the pia 637 2 23 pm, range 500-900 pm). This range of depths includes the lemniscal thalamo-recipient regions of the auditory cortex (Herkenham, 1980;Roger and Arnault, 1989;Vaughan and Foundas, 1982). We begin with an overall description of NB-mediated facilitation of the thalamocortical field response (Metherate and Ashe, 1991), because these data form the basis for the present experiments which focus on a mechanistic explanation for the initial observations.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the variable depth profile of component A, the characteristics of component B described above for the middle to deep layers remained similar across penetrations. Such observations suggest that component A depends on one or more current sinks located in the middle to deep layers, but that this sink occurs across the auditory cortex with a nonhomogeneous, or patchy, distribution, such as that demonstrated for thalamocortical terminations in the rat auditory cortex (Vaughan, 1983;Vaughan and Foundas, 1982). Thus component A could reflect activity of thalamocortical afferents.…”
Section: Differential Nb Modification Of Componentsmentioning
confidence: 97%